Rhododendron groenlandicum (Labrador tea), an antidiabetic plant from the traditional pharmacopoeia of the Canadian Eastern James Bay Cree, improves renal integrity in the diet-induced obese mouse model. (2nd October 2016) - Li, Shilin; Brault, Antoine; Sanchez Villavicencio, Mayra; Haddad, Pierre S.
Abstract: Content Our team has identified Labrador tea [ Rhododendron groenlandicum L. (Ericaceae)] as a potential antidiabetic plant from the traditional pharmacopoeia of the Eastern James Bay Cree. In a previous in vivo study, the plant extract was tested in a high- fat diet (HFD)-induced obese model using C57BL/6 mice and it improved glycaemia, insulinaemia and glucose tolerance. Objective In the present study, we assessed the plant's potential renoprotective effects. Materials and methods Rhododendron groenlandicum was administered at 250 mg/kg/d to mice fed HFD for 8 weeks to induce obesity and mild diabetes. Histological (periodic acid–Schiff (PAS), Masson and Oil Red O staining), immunohistochemical (IHC) and biochemical parameters were assessed to evaluate the renoprotective potential of R. groenlandicum treatment for an additional 8 weeks. Results Microalbuminuria and renal fibrosis were developed in HFD-fed mice. Meanwhile, there was a tendency for R. groenlandicum to improve microalbuminuria, with the values of albumin-creatinine ratio (ACR) reducing from 0.69 to 0.53. Renal fibrosis value was originally 4.85 arbitrary units (AU) in HFD-fed mice, dropped to 3.27 AU after receiving R. groenlandicum treatment. Rhododendron groenlandicum reduced renal steatosis by nearly one-half, whereas the expression of Bcl-2-modifying factor (BMF) diminished from 13.96 AU to 9.43 AU. Discussion and conclusions Taken altogether, the results suggest that R. groenlandicum treatment can improve renal function impaired by HFD.